A Comparison of Sprint Mechanical Parameters Measured With Timing Gates and a Laser Gun - van den Tillaar, Roland; Haugen, Markus Estifanos; Falch, Hallvard Nygaard (Frontiers in Sports and Active Living, 2022)
The aim of the study was to compare sprint mechanical parameters measured with timing gates and a laser gun. Thirty-four female team handball players (age: 17.0  2.3 years, height: 1.70  0.07 m, body mass: 66.7  9.7 kg) performed three 30 m sprints in which the times were measured at 5, 10, 10, 20 and 30 m with timing gates together with the distance over time by a laser gun. The main findings were that with a correction of +0.21 seconds the times and sprint mechanical properties calculated with the spreadsheet of Morin between the systems were similar, but that the peak velocity derived from the automatically calculated MusclelabTM system was significantly higher than the vmax, and lower than the v0 calculated with the spreadsheet. It was concluded that a correction of +0.21 seconds should be used to get correct mechanical properties when measuring with timing gates compared with laser gun measurements on an indoor court. Furthermore, peak velocities based on the spreadsheet of Morin are always slightly lower than the peak velocities measured with a laser gun, due to the low number of data points the velocity–time curve is based on when using the spreadsheet.